Targeting the Endothelin-1 Receptors Curtails Tumor Growth and Angiogenesis in Multiple Myeloma - Russignan, Anna; Dal Collo, Giada; Bagnato, Anna; Tamassia, Nicola; Bugatti, Mattia; Belleri, Mirella; Lorenzi, Luisa; Borsi, Enrica; Bazzoni, Riccardo; Gottardi, Michele; Terragna, Carolina; Vermi, William; et al. (Frontiers in Oncology, 2021)
The endothelin-1 (ET-1) receptors were recently found to mediate pro-survival functions in multiple myeloma (MM) cells in response to autocrine ET-1. This study investigated the effectiveness of macitentan, a dual ET-1 receptor antagonist, in MM treatment, and the mechanisms underlying its activities. Macitentan affected significantly MM cells (RPMI-8226, U266, KMS-12-PE) survival and pro-angiogenic cytokine release by down-modulating ET-1-activated MAPK/ERK and HIF-1alpha pathways, respectively. HIF-1alpha silencing abrogated the ET-1 mediated induction of genes encoding for pro-angiogenic cytokines such as VEGF-A, IL-8, Adrenomedullin, and ET-1 itself. Upon exposure to macitentan, MM cells cultured in the presence of the hypoxia-mimetic agent CoCl2, exogenous ET-1, or CoCl2 plus ET-1, down-regulated HIF-1alpha and the transcription and release of downstream pro-angiogenic cytokines. Consistently, macitentan limited significantly the basal pro-angiogenic activity of RPMI-8226 cells in chorioallantoic membrane assay. In xenograft mouse models, established by injecting NOG mice either via intra-caudal vein with U266 or subcutaneously with RPMI-8226 cells, macitentan reduced effectively the number of MM cells infiltrating bone marrow, and the size and microvascular density of subcutaneous MM tumors. ET-1 receptors targeting by macitentan represents an effective anti-proliferative and anti-angiogenic therapeutic approach in preclinical settings of MM.